Penerapan Pola Konsumsi Tinggi Protein dalam Upaya Pencegahan Anemia pada Remaja Putri - Lisa Rahmawati; Mahdalena Prihatin Ningsih; Rati Purnama Sari; Aprizal Ponda (CV. CENDIKIA JENIUS INDONESIA, 2026)
Anemia remains a major health problem among adolescent girls and can negatively affect growth, learning concentration, intelligence, and academic performance. One of the contributing factors to anemia is inadequate protein intake and an unbalanced diet. This community service program aimed to improve adolescent girls’ knowledge regarding the implementation of a high-protein diet as an effort to prevent anemia. The activity was conducted from September to October 2024 at Taqwa Kurao Mosque, within the working area of Nanggalo Public Health Center, Padang City, involving 50 adolescent girls. The methods included health education sessions, discussions and question-and-answer activities, demonstrations, educational video screenings, and the distribution of booklets and flipcharts. Evaluation was carried out using pre-test and post-test assessments as well as hemoglobin level examinations. The results showed an increase in participants’ knowledge, with the proportion of good knowledge rising from 38% to 64%, while poor knowledge decreased from 22% to 4%. Most participants also had normal hemoglobin levels. In conclusion, education on high-protein dietary patterns effectively improved adolescent girls’ knowledge.